Age, race and viral genotype are associated with the prevalence of hepatitis B e antigen in children and adults with chronic hepatitis B. Issue 7 (2nd May 2019) - Di Bisceglie, Adrian M.; King, Wendy C.; Lisker‐Melman, Mauricio; Khalili, Mandana; Belle, Steven H.; Feld, Jordan J.; Ghany, Marc G.; Janssen, Harry L. A.; Lau, Daryl; Lee, William M.; Ling, Simon C.; Cooper, Stewart; et al.
Abstract: Hepatitis B e antigen (HBeAg) is an important serological marker of hepatitis B virus (HBV) infection and is associated with higher levels of viraemia, increased risk of infectivity to others and increased risk of hepatocellular carcinoma. We analysed HBeAg status in a large cohort of adults and children enrolled in Cohort Studies of the Hepatitis B Research Network, long‐term natural history studies of chronic HBV infection. A cross‐sectional analysis examined factors associated with HBeAg positivity, including demographic and virologic data, across the age spectrum. Among 2241 enrolled participants who met criteria for this analysis, 825 (37%) were seropositive for HBeAg. The prevalence of HBeAg was lower in those with older age, ranging from 85% among those up to 10 years of age to only 12% among those older than 50 years. In addition to age, both race and HBV genotype were independently associated with HBeAg positivity. There was a significant interaction between age and race; the prevalence of HBeAg was significantly higher among Asians > 10‐30 years old vs Whites or Blacks who were >10 to 30 years old and those infected with HBV genotype C. Conversely, the presence of the basal core promoter and precore variants was associated with significantly lower prevalence of HBeAg, even when adjusted for age, race and genotype. These data will provide a better understanding of factors associated with seropositivity for HBeAg and may lead to better strategies for preventing HBV infection and broader indications for antiviral therapy.